2000
DOI: 10.1111/j.1574-6968.2000.tb08896.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic flux in glucose/citrate co-fermentation by lactic acid bacteria as measured by isotopic ratio analysis

Abstract: The flux of carbon into lactic acid, diacetyl and acetoin during the co-metabolism of glucose and citrate by Lactococcus lactis subsp. lactis biovar. diacetylactis has been determined using natural abundance isotopic ratio analysis. During fermentation in the conditions used (glucose, 27.8 mM; citric acid, 13.9 mM; initial pH 6.2-6.4, anaerobic) it is shown that approximately 65% of the carbon source used for the aroma compounds is derived from the carbohydrate. Equally, citrate contributes approximately 30% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 14 publications
4
16
0
Order By: Relevance
“…This metabolic process leads to the formation of a number of minor products important for the organoleptic properties of cheese (19). The present report clearly shows that although E. faecalis FAIR-E 229 cannot catabolize citrate in the presence of glucose, it has the ability to metabolize citrate in milk in the presence of lactose.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…This metabolic process leads to the formation of a number of minor products important for the organoleptic properties of cheese (19). The present report clearly shows that although E. faecalis FAIR-E 229 cannot catabolize citrate in the presence of glucose, it has the ability to metabolize citrate in milk in the presence of lactose.…”
Section: Discussionmentioning
confidence: 62%
“…This conclusion was based on the inability of the lactic acid bacteria to grow in batch cultures to which excess citrate was added as the sole energy source (6,7). Sometimes, lactic acid bacteria need sug- ars, such as glucose or lactose, as cosubstrates in order to consume citrate (7,17,19).…”
Section: Discussionmentioning
confidence: 99%
“…Most of them need a sugar as a co-substrate (Cogan 1987;García-Quintáns et al 1998;Goupry et al 2000). At the beginning of ripening, a low amount of glucose derived from lactose catabolism can be found in cheeses.…”
Section: Discussionmentioning
confidence: 97%
“…Gá lvez, Loiseau, Paredes, Barel, and Guiraud (2007) have shown that citric acid was almost completely degraded before glucose and fructose uptake started during cacao fermentation. Using pure cultures of lactic acid bacteria mainly strains of Lactococcus lactis, Goupry, Croguennec, Gentil, and Robins (2000) have also described a similar phenomenon with citric acid being used first before the sugars.…”
Section: Resultsmentioning
confidence: 96%